Study on Material Integrity of Aluminium 7075 after Heat Treatment Process for Medical Tools - Mohd Noor, Mohammad Norazmeer (IRC, 2020)
Several researchers have conducted studies on the recycling of aluminium waste to reduce carbon footprint and the aim of this study is to conduct heat treatment process on aluminium 7075 waste and determine whether it is a suitable material replacement for medical tools usually made up of stainless steel. Based on its quality, considered to be the strongest aluminium alloy, aluminium 7075 is selected. Heat treatment parameters is decided to be at 110°C, 130°C and 150°C, each having three heating duration of 1, 3 and 5 hours. Density test using gas pycnometer device and Vickers Microhardness test is done after the heat treatment process to see the best results among the set heat treatment parameters compared to the untreated sample.